Cellular interorganelle crosstalk in health and disease states: A glimpse on nephrology-related conditions - Fateme Shamekhi Amiri (Archives of Clinical Nephrology - Peertechz Publications, 2022)
Cellular interorganelle crosstalk in medical sciences is a new discussion of mechanisms and pathways of physiological functions and pathogenesis of diseases. The organelles ("mitochondria", nucleus, lysosome, endoplasmic reticulum, Golgi apparatus) are members of such functional units that are needed to perform specific tasks. Mitochondria are essential metabolic organelles in cells, but they also contribute to iron and calcium homeostasis, as well as in the regulation of apoptosis, and they are increasingly recognized as key signaling platforms. In the kidney, crosstalk between mitochondria with endoplasmic reticulum is at mitochondria-associated endoplasmic reticulum membrane in regulating calcium homeostasis. Another crosstalk between these organelles is about autophagic mechanisms. Autophagy is triggered in the kidney in response to acute kidney injury and supports against kidney injury. High glucose-induced reactive oxygen species can be produced by both enzymatic and nonenzymatic pathways. The nucleotide-binding domain and leucine-rich repeat (NLR) family or nucleotide-binding and oligomerization domain (NOD)-like receptors family pyrin domain containing 3 (NLRP3) inflammasome plays a role in inducing infectious defenses via inflammatory cytokines. The NLRP3 inflammasome is activated by the mitochondria-associated endoplasmic reticulum membrane. It has a role in nephrocalcinosis-related chronic kidney disease. This review article is a summary of interorganelle crosstalk in health and disease states, especially in kidney and nephrology-related conditions.